Mitochondrial genome of Taiwan pig (SUS SCROFA) - Chia-Hsuan Chen; Hsiu-Lin Huang; Hsiu-Ya Yang; Shan-Hu Lai, Neim-Tsu Yen; Mu-Chiou Huang (African Journal of Pig Farming, 2018)
The purpose of this study is to investigate the complete nucleotide sequence of the mitochondrial genome of the Taiwan Lanyu pig (SUS SCROFA) and its phylogenetic relationships with other pig breeds. Thirty-four forward and reverse primers were designed. Sequencing was performed in both directions. The results showed that, the complete sequence of the mitochondrial genome of the Taiwan Lanyu (S. SCROFA) is 16,747 bp, which was deposited in NCBI GenBank (accession number DQ518915). The complete sequence includes two rRNA (12S and 16S), 22 tRNA and 13 mRNA genes. The length of the D-loop region is 1,314 bp and there are 25 repeat sequences (5’-tacacgtgcg) in the region. It seems that there is a significant difference in the D-loop region between the Lanyu and the European Duroc (10 repeats), the landrace (13 repeats), the large white (6 repeats) or Asian pig breeds such as the Japanese wild boar (1 repeat) and the Ryukyu wild boar (1 repeat). The phylogenetic relationships of the Lanyu by comparing the sequence of the mitochondrial genome and the Dloop region of Asian and European pig breeds were investigated. It revealed that, the genetic distance of the Lanyu is high when compared with both the European and Asian pig breeds; the genetic exchange between the Lanyu and other breeds is not frequent. There is also no evidence of genetic exchange or introgression caused by population migration. Therefore, we conclude that the Lanyu is an independent branch among the breeds.